Impact of Social Distancing and Work-From-Home Implementation on Performance with Job Stress as an Intervening Variable: A Case Study at a Government Flight School - Angga Kusuma, Aditya; Fadah, Isti; Hendrian, Hendrian; Cecilia, Cecilia (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the effects of social distancing and Work From Home (WFH) implementation on employee performance, with job stress as a mediating variable, in government-operated flight schools during the COVID-19 pandemic. Employing a quantitative explanatory research method and data analysis using SmartPLS, the findings reveal that social distancing significantly positively impacts employee performance and job stress, with job stress mediating the relationship between social distancing and performance. Conversely, WFH does not significantly affect performance or job stress, attributed to the operational nature of flight training, which requires physical presence and specialized equipment. Job stress, when maintained at moderate levels, positively influences performance by motivating employees to adapt to complex tasks. Recommendations include enhancing training programs, implementing effective WFH strategies, and adopting stress management measures to maintain productivity and well-being. These findings contribute to understanding organizational resilience and employee management in safety-critical sectors during global crises.